2004
DOI: 10.1097/00129039-200409000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Reduced PTEN Expression Is Associated With Poor Outcome and Angiogenesis in Invasive Ductal Carcinoma of the Breast

Abstract: Loss of PTEN expression has been associated with advanced stages of tumor. Tumor angiogenesis is involved in tumor progression. In breast cancer, a high frequency of mutations of the PTEN locus has been reported. However, the prognostic importance of PTEN expression and its correlation with angiogenesis in breast cancer have not been well established. Formalin-fixed, paraffin-embedded tissues from 99 women with a primary diagnosis of invasive ductal carcinoma were evaluated for PTEN expression by immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
32
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 24 publications
5
32
0
1
Order By: Relevance
“…Loss of PTEN expression results in activation of PI3K pathway leading to development of cancer [15,41]. PTEN loss is present in about one third of breast cancer patients, ranging from 15% to 48% [43][44][45][46]. Our study showed that the incidence of PTEN loss was 31.6%, which is consistent with other reported results.…”
Section: Discussionsupporting
confidence: 91%
“…Loss of PTEN expression results in activation of PI3K pathway leading to development of cancer [15,41]. PTEN loss is present in about one third of breast cancer patients, ranging from 15% to 48% [43][44][45][46]. Our study showed that the incidence of PTEN loss was 31.6%, which is consistent with other reported results.…”
Section: Discussionsupporting
confidence: 91%
“…However, the relationship between miR-21 and PTEN in breast cancer is not known. There is evidence that reduced expression of PTEN is associated with tumor progression and poor outcome in breast cancer (11,32,33), but the mechanism of PTEN down-regulation in breast cancer is not clear. Some studies found that the incidence of loss of heterozygosity (LOH) in PTEN was approximately 40% in breast cancer (34,35), but a further study showed that this level of LOH is not sufficient to reduce the expression of PTEN (32).…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports that PTEN has an important role in tumorigenesis of breast cancer (6)(7)(8)(9). It has been shown that reduced PTEN expression is associated with lymph node metastasis, estrogen receptor status, tumor grade, tumor-nodemetastasis (TNM) stage, and microvessel density (MVD), and it may be a valuable prognostic marker in breast cancer (10,11). So, it is reasonable to propose that miR-21 regulating PTEN expression is a ubiquitous mechanism in solid tumors, including breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse mechanisms regulate PTEN expression (Lee et al, 2004;Tsutsui et al, 2005a, b;Abdel-Rahman et al, 2006;Agrawal and Eng, 2006). These range from gene deletion, alterations in mRNA splicing, subcellular localization or epigenetic mechanisms that prevent PTEN transcription.…”
Section: Introductionmentioning
confidence: 99%